Aristotelian Citizenship and Corporate Citizenship: Who is a Citizen of the Corporate Polis? - Sison, Alejo G. 1964- (2011)
After defining the essential elements of Aristotelian citizenship, the article proposes to apply these criteria in its search for the equivalent of a citizen within the corporate polis. It argues that shareholding managers are the best positioned among a firm’s constituents or stakeholders in fulfilling the role of corporate citizens. Greater participation by management not only in the control but also in the ownership of firms brings about benefits for the firm as a whole and for the managers themselves, as organizational citizenship behavior literature, among others, suggests.
Keywords: Organizational Citizenship Behavior; managerial capitalism; Stakeholder Management; Corporate Citizenship; Aristotle